Математическая постановка задачи синтеза компоновочной схемы базовых несущих конструкций - Kondrashov, A. S.; Shelest, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
A mathematical formulation of the problem of structural-parametric synthesis of the layout scheme of basic supporting structures of radio-electronic equipment is proposed and substantiated. A target function is presented that makes it possible to determine the main parameters of constructive modules at various hierarchy levels, taking into account the minimization of volume and cost losses. A generalized geometric model of a constructive module is introduced, suitable for describing modules of any hierarchy level.